PROPAGANDA OF HEALTHY LIGHTS AMONG YOUTH - Kosimova Aziza; Khursandova Sayora; Chorieva Shakhnoza; Rakhmatullaev Zhurabek; Bakhodirov Sardor (American Journals, 2023)
in recent years, attention has been paid to the healthy lifestyle of the younger generation. In this paper, the project "Healthy nation - the strength of the state", developed in the framework of the grant of the Termez Office for the promotion of components of a healthy lifestyle in educational institutions is presented. Within the framework of the project, the stages of introducing the foundations of a healthy lifestyle in higher and secondary educational institutions were developed. The project implementation was successful, goals and tasks were fulfilled, problems were identified.
Keywords: healthy way of life (HLS), the promotion of HLS, educational institutions, the younger generation.